Development of Project-Based Electronic Circuit Learning Modules in the Department of Informatics and Computer Engineering - Satria Gunawan Zain; Ninik Rahayu Ashadi; Nur Alifiah (Journal of Smart Education and Emerging Technology, 2026)
Background/Context: The rapid development of digital technology has increased the need for structured and standardized instructional materials in Electronic Circuits courses within Computer Engineering programs. Existing modules have not systematically integrated circuit simulations, laboratory activities, and project-based learning, leading to inconsistencies across parallel classes and limited support for independent learning. Objective/Purpose: This study aimed to develop a project-based Electronic Circuits e-module that is valid and practical as a standardized digital learning resource for higher education. Method: The research applied a Research and Development approach using the four-D development model, consisting of Define, Design, Develop, and Disseminate stages. Validation was conducted by subject matter experts, media experts, and instrument experts. Product trials involved small-group and large-group testing with students who had taken the Electronic Circuits course. Results: The developed e-module achieved very high validity scores from both material and media experts. Student responses from small and large group trials indicated very positive perceptions regarding usability, clarity of content, and learning support, with overall results categorized as very good. Conclusion: The project-based Electronic Circuits e-module is feasible, practical, and well accepted as instructional material. It has strong potential to support structured, independent, and standardized learning across parallel classes in Computer Engineering education.